2023
DOI: 10.1055/a-2084-5018
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability on Thromboelastography Can Predict the Functional Outcomes in Patients with Acute Ischemic Stroke

Abstract: Background: Thromboelastography (TEG) is a useful test that evaluates the coagulation and fibrinolysis pathways. We investigated the association between the Reaction time (R), a TEG parameter for hypercoagulability, and functional outcome based on the occurrence of hemorrhagic transformation (HT) and early neurological deterioration (END). Methods: We enrolled ischemic stroke patients and performed TEG immediately after the patients’ arrival. The baseline characteristics, occurrence of HT and END, stroke sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“… 12 , 13 , 14 , 15 , 16 , 31 Hypercoagulability, as indicated by thromboelastography (reaction time <5 minutes), has been observed in patients with AIS and negatively correlated with functional independence. 6 , 32 Our findings further suggested a more hyperactive coagulation‐fibrinolysis system in the local ischemic environment surrounding the thrombosis site compared with the systemic circulation, which was evidenced by significant increases in ischemic TAT, PIC, and D‐dimer concentrations. Moreover, we found that increased ischemic, but not systemic, TAT and PIC were independently associated with unfavorable 90‐day functional outcome.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“… 12 , 13 , 14 , 15 , 16 , 31 Hypercoagulability, as indicated by thromboelastography (reaction time <5 minutes), has been observed in patients with AIS and negatively correlated with functional independence. 6 , 32 Our findings further suggested a more hyperactive coagulation‐fibrinolysis system in the local ischemic environment surrounding the thrombosis site compared with the systemic circulation, which was evidenced by significant increases in ischemic TAT, PIC, and D‐dimer concentrations. Moreover, we found that increased ischemic, but not systemic, TAT and PIC were independently associated with unfavorable 90‐day functional outcome.…”
Section: Discussionsupporting
confidence: 51%
“… 3 , 4 , 5 However, there is currently a lack of detailed coagulation‐fibrinolysis profiles during the hyperacute phase, and reliable laboratory tests are not yet available. 6 Hemostatic molecular markers including TAT (thrombin‐antithrombin complex), PIC (plasmin‐α2 plasmin inhibitor complex), t‐PAIC (tissue plasminogen activator‐plasminogen activator inhibitor complex), and sTM (soluble thrombomodulin) are increasingly investigated as potential indicators for an integrated perspective of early activation of the coagulation‐fibrinolysis system. These markers are particularly relevant to endothelial lesions associated with arterial and venous thrombosis.…”
mentioning
confidence: 99%
“…The study from Ryu et al 52 suggested that thromboelastography could predict functional outcomes in acute ischemic stroke. They found a link between a hypercoagulable state (as identified by thromboelastography) and poorer functional independence, symptomatic/asymptomatic hemorrhagic transformation, and early neurological decline.…”
Section: Medical Conditionsmentioning
confidence: 99%